A new North African subspecies in the Helianthemum origanifolium aggregate (H. subg. Plectolobum, Cistaceae) - Crespo, Manuel B.; Alonso, Mª Ángeles; Vicente, Alicia; Villar, José Luis (Phytotaxa, 2016)
The Helianthemum origanifolium aggregate is widely diversified, with several subspecies distributed in the western Mediterranean basin. Populations from Morocco and Algeria have been usually referred either to H. origanigolium subsp. origanifolium or to H. origanifolium subsp. molle, a taxon usually considered an eastern Iberian endemic. Detailed studies of those Moroccan and Algerian populations revealed a unique combination of constant macro- and micromorphological traits, allowing the description of a new subspecies to accommodate them, H. origanifolium subsp. africanum. Some floral and fruit characters, together with SEM observations of the indumentum, were found to be reliable and diagnostic for differentiating the new taxon with regard to the other subspecies of the aggregate. Data on the ecology and distribution are also reported for this new subspecies, as well as affinities and divergences with other closely allied taxa are also discussed.